A produção social do conhecimento na psicologia social brasileira: um estudo descritivo/exploratório a partir da revista Psicologia & Sociedade - Robson Nascimento da Cruz (2008)
The Brazilian Social Psychology suffered especially in the 1960s and 1970s, significant changes that affected both his scientific production as its organization academic, political and institutional. In order to assist in understanding the historical development of the area post-crisis Social Psychology, the study aimed to examine part of their social organization in the Brazilian context, from its main journal, the journal Psychology & Society: Journal of the Association Brazil's Social Psychology (ABRAPSO). To do this, we analyzed all articles appearing in the magazine, between the years 1986 and 2007, these being divided into two distinct phases. Thus, a total of 587 papers, distributed in 36 magazines, was the primary source of this research. Information such as: the institutional and geographical origin of the authors, the pattern of authorship, the formation of the authors, the place of organization of the magazine, the type and the issues of published works, places of carrying out the research described in articles and speeches have been some the information analyzed. The interpretation of these data was made in light of theoretical discussions about the social construction of knowledge, therefore, subjects suchas the History of Science, Sociology of Science and Information Science helped in the analytical work, which allowed, among other things, identify certain patterns organization of the scientific community. The relationship between the context of generating knowledge and institutional home for authors, the change in the types and themes of work and theirduties because of the historical period, the institutional organization of Social Psychology and its possible relationship to the situation of Brazilian science, considering their changes in recent decades, some aspects have been identified and discussed in this research.